Comparative Study of the Feeding Characteristics and Digestion Physiology of Haliotis discus hannai and Haliotis gigantea - Lyu, Mingxin; Gao, Xiaolong; Zhang, Mo; Lin, Shihui; Luo, Xuan; You, Weiwei; Ke, Caihuan (Frontiers in Marine Science, 2021)
Abalones (Haliotis spp.) are typical nocturnal creatures but Haliotis discus hannai is bold and active in the nighttime whereas H. gigantea tends to be timid and inactive. In this study, we quantified and compared the differences in the movement, feeding, and digestive physiology of H. discus hannai and H. gigantea as well as the potential molecular mechanisms based on video observations and the expression levels of feeding regulation-related genes. The feeding behaviors of both species were characterized by significant circadian rhythms (P < 0.05). However, the distance moved and cumulative duration of movement were 2.61 and 1.94 times higher in H. discus hannai than those in H. gigantea, respectively, over the 24 h cycle. The cumulative duration of feeding by H. discus hannai was only 1.15 times that of H. gigantea, but the feeding time by H. gigantea as a percentage of the cumulative duration of movement was up to 94.6%, and only 56.0% by H. discus hannai. The peaks of the α-amylase activity and NPF expression level in both species as well as the peak OX2R expression level in H. gigantea occurred during 20:00–00:00. By contrast, the peaks of the alginate lyase activity and NPYR expression level in H. discus hannai occurred at 16:00 when the feeding proportion was significantly higher for H. discus hannai than that for H. gigantea. These initial findings quantify specific behavior parameters, thereby providing a reference for the selection of appropriate feeding strategies and the proliferation of abalone by bottom sowing.